2019
DOI: 10.1038/s41467-019-09492-4
|View full text |Cite
|
Sign up to set email alerts
|

The cyclooxygenase-1/mPGES-1/endothelial prostaglandin EP4 receptor pathway constrains myocardial ischemia-reperfusion injury

Abstract: The use of nonsteroidal anti-inflammatory drugs that inhibit cyclooxygenase (COX)-1 and COX-2, increases heart failure risk. It is unknown whether microsomal (m) prostaglandin (PG) E synthase (S)-1, a target downstream of COX, regulates myocardial (M) ischemia/reperfusion (I/R) injury, a key determinant of heart failure. Here we report that COX-1 and mPGES-1 mediate production of substantial amounts of PGE 2 and confer cardiac protection in MI/R. Deletion of mPges-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 48 publications
1
46
0
2
Order By: Relevance
“…Elevation of IL-6 and IL-1β can induce cardiomyocyte apoptosis and reduce ventricular wall compliance and cause coronary microvascular endothelial inflammation [42]. Study shows that the use of nonsteroidal anti-inflammatory drugs that inhibit PTGS1 and PTGS2 increases the risk of HF as they can reduce prostaglandin E generation that can protect the heart [43]. Both ADRA2C and ADRB1 are involved in the regulation of myocardial contractility, heart rate, and blood pressure [44].…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of IL-6 and IL-1β can induce cardiomyocyte apoptosis and reduce ventricular wall compliance and cause coronary microvascular endothelial inflammation [42]. Study shows that the use of nonsteroidal anti-inflammatory drugs that inhibit PTGS1 and PTGS2 increases the risk of HF as they can reduce prostaglandin E generation that can protect the heart [43]. Both ADRA2C and ADRB1 are involved in the regulation of myocardial contractility, heart rate, and blood pressure [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of mPGES-1 in pathological cardiac remodeling and heart dysfunction is still in debate. Although studies had reported impaired post-ischemic heart function and cardiac remodeling in mPGES-1 deficient mice (Degousee et al, 2008;Zhu et al, 2019), we and others failed to observe any adverse influence on cardiac remodeling after mPGES-1 was deleted globally or selectively in myeloid cells (Chen et al, 2019;Wu et al, 2009b). Moreover, in a model of Ang II mediated cardiac remodeling, although lack of mPGES-1 did not affect cardiac hypertrophy and fibrosis, nevertheless poor cardiac function was observed (Harding, Yang, He, & This article has not been copyedited and formatted.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial I/R injury protocol. The induction of myocardial I/R injury in the present study was performed as previously described (17), with a few modifications. Briefly, rats were anesthetized by the intraperitoneal injection of pentobarbital sodium (40 mg/kg) and were mechanically ventilated.…”
Section: Animals and Treatmentsmentioning
confidence: 99%